"What would Voltaire say?": Voltaire’s exchange value in the correspondence of Catherine the Great - Rubin-Detlev, K (La Société des études Voltairiennes, 2018)
Christiane Mervaud has demonstrated how, in his correspondence, Voltaire reduced Catherine the Great to an ‘emblème’ and a ‘signe de ralliement’: in his letters she became a symbol of the protection of the arts and the struggle for religious toleration, and, via this transformation, her name became a publicity tool for promoting the cause of the philosophes. But the complementary question has not yet been asked: what was Voltaire’s emblematic value in Catherine the Great’s correspondence?